De-prosecution and death: a reply to an imprecise and ideological critique - Hogan, Thomas P. (Criminology & public policy, 2023)
In an original article, I analyzed a potential causal link between the policy of de-prosecution in Philadelphia and an increase in homicides. Utilizing the traditional synthetic control method with extensive descriptive data and a donor pool of the other 99 largest cities in the United States, the results demonstrated a statistically significant increase of over 74 homicides per year in Philadelphia during 2015-19 associated with de-prosecution (p<.05). A reaction essay addressing the original article on de-prosecution has been submitted. In this reply, I correct inaccuracies in the reaction essay, explain the validity of methodological choices, discuss the reaction's misunderstanding of certain quantitative issues, and expose the ideological purposes of the reaction. In addition, I have included updated parallel research addressing the issue of de-prosecution and examine the theoretical impact of the Covid-19 pandemic on the interaction between de-prosecution and homicides.